Participation and Level of Satisfaction of Member Farmers in Dairy Cooperative Societies of Jammu & Kashmir - Sankhala, Gopal — (Indian Journal of Dairy Science, 2016)
The present study was conducted with the objective of finding out the member’s participation and their satisfaction in the working of dairy co-operative societies under Jammu and Kashmir Milk Producers Co-operative Limited (JKMPCL). The primary data was collected from 160 respondents by using pre tested and structured interview schedule. The sample of respondents was selected by stratified random sampling technique. The societies registered with the co-operatives for last three consecutive years and the members supplying milk to co-operatives for at least 180 days a year were selected for the study. The results revealed that majority (75.00%) of the respondents never participated in co-operative societies for reasons other than the sale of milk. Out of the participating members major percentage was found actively involved in meetings of the co-operative societies. The study also reported that majority (66.25%) of the respondents never viewed the proceedings of the official records of the societies. Such low level of participation indicated that they viewed cooperative societies as mere collection centers. Further it was found that majority of the respondents were satisfied with the selected indicators other than the provision of technical inputs and services for which all the respondents were found unsatisfied due to their absolute lack in the societies. The study concludes that the participation and satisfaction of the members could be improved by starting provision of technical inputs and services in co-operative societies; which will further lead to their increased sense of belongingness and commitment to the co-operative societies.